β-Resorcylic acid prevents MASLD in ob/ob mice by modulating lipid metabolism and inflammation in the liver - Sergio López-Herrador; Sara Torres-Rusillo; Pilar González-García; Laura Jiménez-Sánchez; Julia Corral-Sarasa; Mohammed Bakkali; M. Elena Díaz-Casado; Luis C. López (Pharmacological Research)
Metabolic dysfunction-associated steatotic liver disease (MASLD) represents a significant global health challenge. MALSD is primarily driven by metabolic dysfunction, including mitochondrial dysregulation. Here, we show that β-resorcylic acid (β-RA), a naturally derived phenolic molecule known to target mitochondrial Coenzyme Q biosynthesis, reduces hepatic steatosis and inflammation, thus preventing the progression to MASH in the leptin-deficient ob/ob mouse model. Early transcriptomic analyses revealed that β-RA activates HNF4α, a key regulator of lipid metabolism, leading to reductions in both macrosteatosis and microsteatosis. Furthermore, β-RA suppressed neutrophil degranulation and downregulated inflammatory markers, including Mpo, Anxa5, and Ly6d. These effects correlated with reductions in markers of hepatic injury, such as serum ALT and AST levels and hepatocyte ballooning. In line with these in vivo findings, β-RA also reduced neutral lipid accumulation in human HepG2 hepatocytes exposed to oleic and palmitic acids, confirming its anti-steatotic effect in a translational cellular model of fatty acid-induced steatosis. Overall, these findings identify β-RA as a promising therapeutic candidate for MASLD, with the ability to prevent MASH progression independently of leptin. Further research is needed to explore its translational potential in human MASLD and its integration with other therapies.